S91 Investigating the role of AKAP13 in epithelial cells on TGF-β activation. (12th November 2019) - Porte, J; John, A; Jenkins, RG; Organ, L
Abstract : Rationale: We recently identified a polymorphism associated with the AKAP13 gene resulted in higher levels of AKAP13 gene expression and Idiopathic pulmonary fibrosis (IPF) susceptibility. Furthermore, higher expression of AKAP13 were associated with diseased epithelium. 1 AKAP13 is a Rho-GEF for RhoA, a key intermediate signal in the activation of the TGF-β activating integrin, αvβ6, in lung epithelial cells. However, the role for AKAP13 in the lung is still not understood. Aim: To investigate the role of AKAP13 in lung epithelial cells, including Rho-A and TGFβ. Method: Localisation of protein expression of AKAP13 and αvβ6 was assessed in IPF human lung tissue via immunohistochemistry, using serial sections. AKAP13 gene expression was assessed via qPCR in primary human lung fibroblasts (normal, n=3; IPF, n=4) and primary epithelial cell lines (small airway SAEC, n=9; human bronchial HBEC, n=4). Immortalised human bronchial epithelial cells (iHBECs) were treated with AKAP13 siRNA to knockdown expression of AKAP13 and assessed for changes to mRNA after 48 hrs. iHBECs were treated with 10uM of A13, an inhibitor for AKAP13-RhoA interaction, to assess for functional changes to Rho-A activation in response to LPA. Results: Assessment of serial lung sections from IPF patients (n=106) show that positive staining for AKAP13 and αvβ6 is observed in lung epithelial cells, within the same regions of lung. AKAP13 gene expression was found to be 19-fold higher in epithelial cells, compared to fibroblasts, which had very low expression for AKAP13 (both normal and IPF), confirming our previous and current immunohistochemistry findings. 1 Knockdown of the AKAP13 gene in iHBECS also resulted in a significant decrease in ITGB6 expression, the gene for αvβ6 (n=4, p=0.03). In addition, treatment of iHBECS with 10uM of A13 was able to supress RhoA activation in response to LPA. Conclusion: AKAP13 expression is found predominantly in epithelial cells in the lung. AKAP13 appears to regulate RhoA activation in iHBECs and influence αvβ6 expression. This suggests that it is involved in the RhoA- αvβ6 pathway that drives TGF-β activation in epithelial cells Reference: Allen RJ, et al . Genetic variants associated with susceptibility to idiopathic pulmonary fibrosis in people of European ancestry: a genome-wide association study. The Lancet Respiratory Medicine 2017;5 (11):869–880.